2019
DOI: 10.1002/dmrr.3256
|View full text |Cite
|
Sign up to set email alerts
|

Surgical revascularization and reconstruction procedures in diabetic foot ulceration

Abstract: This article summarizes surgical procedures for preservation of the foot in diabetic patients with peripheral artery disease. Distal bypass surgery performed to perigeniculate arteries and to an isolated ‘blind’ popliteal segment with visible collaterals can be performed with limb salvage rates close to what can be achieved with standard bypass to crural arteries. This is also the case when performing bypass to the dorsalis pedis artery. Bypass to the medial or lateral plantar artery or to the lateral tarsal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…TcPO2 levels was recorded in all patients with a median number of measurements per patients of 12 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Median value increased from 8 + 2 mmHg (4-32 mmHg) before the AVF creation to 56 + 4 mmHg (48-75 mmHg) at 6 months after the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TcPO2 levels was recorded in all patients with a median number of measurements per patients of 12 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Median value increased from 8 + 2 mmHg (4-32 mmHg) before the AVF creation to 56 + 4 mmHg (48-75 mmHg) at 6 months after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality after major amputation in patients with diabetes is high, with 5-year mortality between 52% and 80% in various studies and is closely related to amputation level. 2 Revascularization, through either endovascular or surgical technique, could prevent amputation by increasing blood supply and, thereby, relieving pain and allowing wound healing. However, in about 14-20% of patients, the distribution of occlusive lesions is such that routine surgical or endovascular techniques cannot be applied.…”
Section: Introductionmentioning
confidence: 99%
“…The recipient vessels dorsalis pedis artery, the tarsal artery, and the medial or lateral plantar arteries in patients with critical limb ischemia. When compared to endovascular treatments like percutaneous transluminal angioplasty, bypass surgery has been considered the more effective type of revascularization [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Vascular intervention can ameliorate the blood supply to lower extremity blood vessels and supply ischemic tissue oxygen to a certain extent. [23][24][25] Vascular intervention is currently the main treatment for refractory ulcers and chronic ischemic disease of the lower extremities. Our study showed that patients in the recurrence group received vascular interventions five times more often than those in the initial group (see Table 3).…”
Section: Discussionmentioning
confidence: 99%